Moral Value in “Wonder” Movie Directed by Stephen Chbosky (2017) - Arfani, Sri; Puspita, Vira Ayu (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
Moral value is a very important thing in our life and it becomes a basic need of every human in the world. This research conducts a literary analysis focused on the moral values embodied in the film "Wonder". In this research, the author focuses on discussing the moral values embodied in Stephen Chbosky's "Wonder" (2017) using a qualitative descriptive method based on Linda and Eyre’s theory of moral values. The objective is to describe the moral values exhibited in “Wonder” movie. The result showed there were nine types of moral values found in “Wonder” movie. There were total of 13 moral values . They were 9 values pertaining to being (1) Honesty, (2) Bravery, (3) Peace Ability, (4) Confidence Individuality, (5) Hard Work, (6) Loyal and Trustworthy, (7) Love and Affection, (8) Sensitive and Not Selfish, and (9) Humble and Caring. The result showed the Value of giving as the most dominant value in the movie based on Linda and Eyre’s theory. All data interpretations are contextualized within the film's narrative.